1999
DOI: 10.1001/archpedi.153.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Fragmentation in Children With Atopic Dermatitis

Abstract: To characterize the sleep pattern of children with atopic dermatitis in clinical remission.Methods: Fourteen children with atopic dermatitis, with a mean ± SD age of 6 ± 2 years, were recruited consecutively from a pediatric dermatology clinic. No participant had any other medical or psychiatric illness. The control group (n = 9, mean age 7 ± 1.8 years) was composed of children with mild "benign" snoring and no evidence of respiratory disturbance during sleep. All participating children were evaluated by forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 24 publications
8
81
0
Order By: Relevance
“…Indeed, family stress explained some of the increased risk of childhood asthma. Asthma and hay fever symptoms, and atopic dermatitis-related pruritis, may be the cause of disrupted sleep in cross-sectional studies of older children [2,18,47,48]. We also recognise the possibility that reverse causation may be responsible for our findings in infants because wheeze during infancy can cause nocturnal awakening and is a marker for future asthma [28,49].…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, family stress explained some of the increased risk of childhood asthma. Asthma and hay fever symptoms, and atopic dermatitis-related pruritis, may be the cause of disrupted sleep in cross-sectional studies of older children [2,18,47,48]. We also recognise the possibility that reverse causation may be responsible for our findings in infants because wheeze during infancy can cause nocturnal awakening and is a marker for future asthma [28,49].…”
Section: Discussionmentioning
confidence: 67%
“…A possible limitation of the present study is the ''first-night effect'', which may affect the sleep architecture of individuals during their first night of the PSG evaluation. However, in a previous study we have shown that the only significant change between two consecutive nocturnal PSG studies was in REM sleep [25]. No change was noted in SWA in the comparison group between the two PSG studies, where each patient served as their own control; thus, we do not think the first-night effect affects our interpretations.…”
Section: Subjectsmentioning
confidence: 60%
“…A previous study also revealed that scratching accounted for only 15% of arousals in patients with AD. 11 Therefore, scratching movements play a part in the sleep disturbance of patients with AD, but are unlikely the sole etiology.…”
Section: Figurementioning
confidence: 99%
“…11 Melatonin is a hormone secreted by the pineal gland that is essential for regulating the circadian rhythm. 12 Dysfunction in the diurnal secretion of melatonin in patients with AD has been reported, 13 but its association with their sleep disturbance has not been studied.…”
mentioning
confidence: 99%